Neurodegenerative and functional signatures of the cerebellar cortex in m.3243A > G patients. Issue 1 (3rd February 2022) - Haast, Roy A. M.; De Coo, Irenaeus F. M.; Ivanov, Dimo; Khan, Ali R.; Jansen, Jacobus F. A.; Smeets, Hubert J. M.; Uludağ, Kâmil
Abstract: Mutations of the mitochondrial DNA are an important cause of inherited diseases that can severely affect the tissue's homeostasis and integrity. The m.3243A > G mutation is the most commonly observed across mitochondrial disorders and is linked to multisystemic complications, including cognitive deficits. In line with in vitro experiments demonstrating the m.3243A > G's negative impact on neuronal energy production and integrity, m.3243A > G patients show cerebral grey matter tissue changes. However, its impact on the most neuron dense, and therefore energy-consuming brain structure—the cerebellum—remains elusive. In this work, we used high-resolution structural and functional data acquired using 7 T MRI to characterize the neurodegenerative and functional signatures of the cerebellar cortex in m.3243A > G patients. Our results reveal altered tissue integrity within distinct clusters across the cerebellar cortex, apparent by their significantly reduced volume and longitudinal relaxation rate compared with healthy controls, indicating macroscopic atrophy and microstructural pathology. Spatial characterization reveals that these changes occur especially in regions related to the frontoparietal brain network that is involved in information processing and selective attention. In addition, based on resting-state functional MRI data, these clusters exhibit reduced functional connectivity to frontal and parietal cortical regions, especially in patients characterized by (i) a severe disease phenotype and (ii) reduced information-processing speed and attention control. Combined with our previous work, these results provide insight into the neuropathological changes and a solid base to guide longitudinal studies aimed to track disease progression. Abstract : The m.3243A > G mutation is known to affect brain tissue integrity. In this work, Haast et al . identified neurodegenerative and functional changes across the cerebellum in m.3243A > G patients using high-resolution 7 T MRI data. Together, the presented results expand our understanding of the mutation's neurological expression. Graphical Abstract: Graphical Abstract